Triangle Park: addressing residual urban space - Williams, Shannon L. (Kansas State University, 2010)
In the 2009-2010 academic year at the Kansas City Design Center, four students undertook a design project seeking to transform an underutilized traffic median into a usable urban public space. The space, known as “Triangle Park,” is located at Avenida Cesar E. Chavez (West 23rd Street), West Pennsylvania Avenue, and Southwest Boulevard in Kansas City, Missouri. This report describes the existing site conditions and challenges to creating an inviting public space. The report explains how the students arrived at the finalized design using precedent studies, multiple design iterations, and community input from the Westside and Crossroads neighborhood stakeholders. The finalized design focuses on providing connectivity between people, the site, and the city as a whole. Opportunities for connection are offered by improved pedestrian circulation and a comfortable, well-defined outdoor space. Three major structural interventions are proposed: an illuminated overhead canopy beneath the Interstate-35 overpass provides shelter for pedestrians; a raised walking path enhances an already prominent pedestrian route; and a wooden deck provides opportunities for sitting and lingering. The ability of the design to meet the community’s stated needs and to serve as a social public space is evaluated to determine the likelihood of positive and worthwhile project outcomes.
Keywords: Design; Interdisciplinary; Residual space; Public space; Highway overpass; Community; Architecture (0729); Urban and Regional Planning (0999)